Syntaxonomical revision of the Triseto flavescentis-Polygonion bistortae alliance in the Carpathians - Katarína Hegedüšová; Joanna Korzeniak; Jana Májeková; Adrian Stoica; Gheorghe Coldea; Anna Kuzemko; Vasyl Budzhak; Alla Tokaryuk; Illya Chorney; Iveta Škodová (Plant Biosystems, 2021)

Ecology and species distribution pattern of Soldanella sect. Soldanella (Primulaceae) within vegetation types in the Carpathians and the adjacent mountains - Milan Valachovič; Eliška Štubňová; Dušan Senko; Judita Kochjarová; Gheorghe Coldea (Biologia, 2019)

Genetic diversity in widespread species is not congruent with species richness in alpine plant communities - Pierre Taberlet; Niklaus E. Zimmermann; Thorsten Englisch; Andreas Tribsch; Rolf Holderegger; Nadir Alvarez; Harald Niklfeld; Gheorghe Coldea; Zbigniew Mirek; Atte Moilanen; Wolfgang Ahlmer; Paolo Ajmone Marsan; et al. (Ecology Letters, 2012)
The Convention on Biological Diversity ( CBD ) aims at the conservation of all three levels of biodiversity, that is, ecosystems, species and genes. Genetic diversity represents evolutionary potential and is important for ecosystem functioning. Unfortunately, genetic diversity in natural populations is hardly considered in conservation strategies because it is difficult to measure and has been hypothesised to co‐vary with species richness. This means that species richness is taken as a surrogate of genetic diversity in conservation planning, though their relationship has not been properly evaluated. We tested whether the genetic and species levels of biodiversity co‐vary, using a large‐scale and multi‐species approach. We chose the high‐mountain flora of the Alps and the Carpathians as study systems and demonstrate that species richness and genetic diversity are not correlated. Species richness thus cannot act as a surrogate for genetic diversity. Our results have important consequences for implementing the CBD when designing conservation strategies.

In vitro propagation and cryopreservation of Romanian endemic and rare Hypericum species - Ana Coste; Adela Halmagyi; Anca Livia Butiuc-Keul; Constantin Deliu; Gheorghe Coldea; Bogdan Hurdu (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Effects of plant growth regulators and elicitors on production of secondary metabolites in shoot cultures of Hypericum hirsutum and Hypericum maculatum - Ana Coste; Laurian Vlase; Adela Halmagyi; Constantin Deliu; Gheorghe Coldea (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Alpine–subalpine species richness of the Romanian Carpathians and the current conservation status of rare species - Gheorghe Coldea; Ilie-Adrian Stoica; Mihai Puşcaş; Tudor Ursu; Adrian Oprea (Biodiversity and Conservation, 2009)